PRODUK TABUNGAN ANAK SEKOLAH (TANAS) PADA BANK BKC SEBAGAI SALAH SATU ALTERNATIF DANA PENDIDIKAN ANAK - Rizkia Shafa Cattleya Azzahra; Siti Nila Rokhmana; Muhamad Aminudin (UI Cirebon (Universitas Islam Cirebon), 2022)
The education fund is one of the most important things for a child to receive at school, which makes it an attractive thing for both Banks and insurance companies to make a child’s education product, the BKC bank, which is one of the cirebon Banks, also brings out the child’s savings products (tanas). The goal of this study is to understand that children’s savings products at BKC bank could be one of the alternatives to child education. Hence, the study USES descriptive qualitative methods and the techniques used are interviews and observations. Studies suggest that schoolchildren’s savings may provide an alternative to the child’s education fund with the benefit of educating and enhancing children’s interest in savings early on, that all child education needs are readily available, and participating in development in cirebon district.